Assessment of pesticide residues in vegetables produced in central and eastern Ethiopia - Dinede, Getachew; Bihon, Wubetu; Gazu, Lina; Foukmeniok Mbokou, Serge; Girma, Sisay; Srinivasan, Ramasamy; Roothaert, Ralph; Grace, Delia; Gashaw, Habtamu; Knight-Jones, Theodore J. D. (Frontiers in Sustainable Food Systems, 2023)
In Ethiopia, pesticides are widely used in vegetable production. However, if used incorrectly they may harm consumers of vegetables contaminated with pesticide residues, as well as producers handling the pesticides and lead to ecological damage. We performed a cross-sectional survey to assess pesticide residues level in vegetables produced in central and eastern Ethiopia. A total of 232 vegetable samples (91 tomatoes, 106 cabbages and 35 Swiss chard) were collected from fields and retail markets, and were screened for 35 pesticides (20 organophosphate, 14 organochlorine and a synergist, piperonyl butoxide) using GC-MS analysis. Pesticides residues were detected in 60% of Swiss chard, 47% of cabbage and 45% of tomato samples. Two or more pesticides were detected in 20% of cabbages, 13% of tomatoes and over half of Swiss chard samples. Bendiocarb, diazinon, endrin, piperonyl butoxide, profenofos and propargite were detected, but only diazinon, propargite and profenofos had residual values above EU Maximum Residue Level (MRL), with diazinon commonly detected at relatively high levels. While 15% of the analyzed samples had pesticide residues above EU MRL, 10% of cabbages and tomatoes, and nearly half of Swiss chard samples had pesticide concentration exceeding EU MRL. However, none of the tested samples had residues exceeding Codex Alimentarius Commission (Codex) MRLs. But it is unlikely that we capture the margins of the distribution of pesticide contamination and rare, higher exposures are anticipated. We recommend monitoring and regulation of pesticides usage, with promotion of good agricultural practices.